Grain dust explosions up slightly in 1985 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Twenty-two dust explosions were reported in the U.S. according to data compiled by Ralph Regan, FGIS Safety Director and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This compares to 20 in 1984 and a 10 year average of 21 explosions.
Keywords: Grain dust; Dust explosions